2022
DOI: 10.1111/eva.13351
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection signatures in farmed Colossoma macropomum from tropical and subtropical regions in South America

Abstract: Tambaqui or cachama ( Colossoma macropomum ) is one of the most important neotropical freshwater fish used for aquaculture in South America, and its production is concentrated at low latitudes (close to the Equator, 0°), where the water temperature is warm. Therefore, understanding how selection shapes genetic variations and structure in farmed populations is of paramount importance in evolutionary biology. High‐throughput sequencing to generate genome‐wide data for fish species allows f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Some individual signals were placed in/or cover genes that indicated a very specific selective process such as the top DCMS hit (interferon‐inducible very large GTPase 1‐like) which might be a result of pressure due to pathogenic agents (Kim et al, 2012 ; Meunier & Broz, 2016 ; Pilla‐Moffett et al, 2016 ). Notably, genomic regions harbouring genes with immunity‐related functions have been recently pinpointed as putative selection signatures through the application of high‐density genotyping technologies in various farmed fish like Atlantic salmon ( Salmo salar ) (Gutierrez et al, 2016 ; López et al, 2019 ), coho salmon ( Oncorhynchus kisutch ) (López et al, 2021 ), rainbow trout ( Oncorhynchus mykiss ) (Cádiz et al, 2021 ), tambaqui ( Colossoma macropomum ) (Agudelo et al, 2022 ) and Nile tilapia ( Oreochromis niloticus ) (Cádiz et al, 2020 ). Such pattern, consistent across several different species, could be influenced by the fact that usually farmed fish are either directly selected for traits associated with disease resistance or due to the exposure to high levels of pathogens, strong selective pressure is applied in those genomic regions (López et al, 2015 ; Zueva et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some individual signals were placed in/or cover genes that indicated a very specific selective process such as the top DCMS hit (interferon‐inducible very large GTPase 1‐like) which might be a result of pressure due to pathogenic agents (Kim et al, 2012 ; Meunier & Broz, 2016 ; Pilla‐Moffett et al, 2016 ). Notably, genomic regions harbouring genes with immunity‐related functions have been recently pinpointed as putative selection signatures through the application of high‐density genotyping technologies in various farmed fish like Atlantic salmon ( Salmo salar ) (Gutierrez et al, 2016 ; López et al, 2019 ), coho salmon ( Oncorhynchus kisutch ) (López et al, 2021 ), rainbow trout ( Oncorhynchus mykiss ) (Cádiz et al, 2021 ), tambaqui ( Colossoma macropomum ) (Agudelo et al, 2022 ) and Nile tilapia ( Oreochromis niloticus ) (Cádiz et al, 2020 ). Such pattern, consistent across several different species, could be influenced by the fact that usually farmed fish are either directly selected for traits associated with disease resistance or due to the exposure to high levels of pathogens, strong selective pressure is applied in those genomic regions (López et al, 2015 ; Zueva et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, tambaqui or cachama ( Colossoma macropomum ), one of the most important neotropical freshwater fish used for aquaculture in South America, was investigated using the ddRAD sequencing approach in farmed populations from Brazil, Colombia and Peru to study the effects of recent artificial selection and domestication. Agudelo et al 232 identified several genomic regions potentially associated with stress tolerance and immunity, suggesting local adaptation to the culture environment.…”
Section: Signatures Of Domestication and Selectionmentioning
confidence: 99%
“…History of domestication and artificial selection in aquaculture species is much more recent, and in some cases very incipient (López et al, 2015 ). Selection signatures, generated during the early domestication and recent selective breeding, have been assessed at a genome‐wide scale in important farmed fish species, including Atlantic salmon (Gutierrez et al, 2016 ; López, Benestan, et al, 2019 ; López, Linderoth, et al, 2019 ; Naval‐Sanchez et al, 2020 ), rainbow trout (Cádiz et al, 2021 ), coho salmon (López et al, 2021 ), Nile tilapia ( Oreochromis niloticus ; Cádiz et al, 2020 ; Hong Xia et al, 2015 ), channel catfish (Sun et al, 2014 ), common carp ( Cyprinus carpio ; Xu et al, 2019 ), turbot ( Scophthalmus maximus ; Aramburu et al, 2020 ), Australasian snapper ( Chrysophrys auratus ; Baesjou & Wellenreuther, 2021 ), gilthead seabream ( Sparus aurata ; Gkagkavouzis et al, 2021 ) tambaqui ( Colossoma macropomum ; Agudelo et al, 2022 ), as well as in shellfish farmed populations, including bay scallop ( Argopecten irradians ; Wang et al, 2021 ), Yesso scallop ( Mizuhopecten yessoensis ; Lv et al, 2022 ), European flat oyster ( Ostrea edulis ; Vera et al, 2019 ) and Pacific oyster ( Crassostrea gigas ; Hu et al, 2021 ; Jiao et al, 2021 ). These studies have used dense genome‐wide genotypes to identify genomic regions harboring genes affecting important phenotypes in farmed fish and shellfish.…”
Section: Domestication and Artificial Selectionmentioning
confidence: 99%
“…, common carp (Cyprinus carpio;Xu et al, 2019), turbot (Scophthalmus maximus;Aramburu et al, 2020), Australasian snapper (Chrysophrys auratus;Baesjou & Wellenreuther, 2021), gilthead seabream (Sparus aurata;Gkagkavouzis et al, 2021) tambaqui (Colossoma macropomum;Agudelo et al, 2022), as well as in shellfish farmed populations, including bay scallop (Argopecten irradians;Wang et al, 2021), Yesso scallop (Mizuhopecten yessoensis;Lv et al, 2022), European flat oyster (Ostrea edulis;Vera et al, 2019) and Pacific oyster (Crassostrea gigas;Hu et al, 2021;Jiao et al, 2021).These studies have used dense genome-wide genotypes to identify genomic regions harboring genes affecting important phenotypes in farmed fish and shellfish. In general, studies on genomic footprints of domestication and artificial selection in aquaculture species have identified loci, which are putatively associated to adaptation to different biotic and abiotic conditions imposed by farming and management practices, as well as traits improved by selective breeding.Genes enriched within the loci underlying selection aquaculture populations are generally associated with growth, immune response, behavior and reproduction, indicating that these processes are important during the adaptation to captivity and also favored by recent human-driven selection.…”
mentioning
confidence: 99%